Berwisata Budaya di Pura Desa Batuan: Menggugah Kesadaran Multikulturalisme - Ni Wayan Karmini (Pusat Kajian Bali Universitas Udayana, 2016)
Temple has been one of the popular tourist attractions in Bali. This article is intended to discuss the development of Village Temple at Batuan, Sukawati, Gianyar as one of the cultural tourist attractions and the tourists’ response to it. This present study is a qualitative one. The data were collected through observation, library research and in depth interview in which 12 informants were interviewed. They were the management of Village Temple at Batuan and the tourists visiting the temple. The data were analyzed descriptively, qualitatively and interpretatively using the theory of commodification. The result of the study shows that the temple, which has been developed as a tourist attraction since 1980s, turns out to have improved the local people’s economy and cultural tradition. Therefore, it is suggested that the temple should be perpetually maintained and developed as a tourist attraction. The result of the study also shows that the tourists visiting the temple can acquire the knowledge of the Balinese culture. They become familiar with the religious tradition and cultural art of the Balinese people. Such recognition of the existence of the Bali Hindu has been one of the forms of the attitude that religious pluralism is appreciated.